Efektivitas E-Learning Sebagai Media Pembelajaran Mata Kuliah Teori Ekonomi Mikro (Studi Pada Kegiatan Rpl Daring Dengan Ikip Gunung Sitoli) - Syafaatul Hidayati; Syamsul Anwar (Universitas Hamzanwadi, 2021)
The purpose of this study was to determine the effectiveness of E-learning as a Learning Media for Microeconomic Theory Courses (Studies on Online RPL Activities with IKIP Gunung Sitoli). This study refers to a quantitative research approach with a quasi-experimental approach. The trial subjects in this study were students who were involved in the Online RPL for the Microeconomic Theory Course, totaling 20 students. The prerequisite test used is the normality test. Test the hypothesis to determine the effectiveness of e-learning as a medium of learning in microeconomic theory courses with the statistical technique of Paired Sample T Test. Based on the test results indicate that the data is normally distributed, with the Shapiro-Wilk sig pretest value of 0.074 0.05 and the posttest sig value of 0.18 0.05. The value of sig 0.000 0.05 (5 %), means that H0 is rejected. Thus e-learning as a learning medium in microeconomic theory courses can be said to be effective.